Microbial carbonate rocks: composition, structures, textures, mechanisms and environments of formation. Emergence of the doctrine of microbial formations and their forms. Article 1 - V. G. Kuznetsov; L. M. Zhuravleva (Известия высших учебных заведений: Геология и разведка, 2022)
Introduction. Concepts describing bacterial effects on mineral formation and, first of all, on the formation of carbonate deposits, started to appear late in the 19th century both in Russia and globally. The precipitation of materials was demonstrated to take place directly at the sedimentation stage and continue in the formed precipitate during diagenetic processes. Research in this direction has recently intensified. Rocks and their constituent parts formed as a result of bacterial activity have been referred to as “biosedimentary structures” or “microbiolites”.Aim. The paper presents the results of generalization and systematization of accumulated research data on the abovementioned forms.Materials and methods. In addition to literature materials, carbonate rocks of various ages – from the Vendian and Lower Cambrian of the Siberian platform to the Crimea Neogene and sediments of contemporary oceans – were examined using macro- and microscopic (mainly) methods of studying and describing specific objects. Article 1 considers the main morphological types of such carbonate formations, both in the form of individual structural components of sedimentary rocks and rocks themselves with peculiar structural characteristics.Results. Two main morphological groups of carbonate microbiolites were identified and characterized. The first group represents individual and independent forms of carbonate material, both of calcite, highly magnesian-dolomite and even pure magnesite composition. This type includes mineralized precipitates of bacterial forms represented by coccolites, tubules, filaments, as well as by plate and sheet structures – mineralized glycocalyx traces. In addition, this group features isolated carbonate objects, familiar to lithologists, including oolites, oncolites, microclusters of pelitomorphic carbonate materials, thrombolites and, apparently, such specific formations as tubiphytes, etc. The second group includes laminated forms of stromatolites with their specific internal structure, as well as mineralized microbial films and mats with a complex structure, etc.Conclusions. In the overwhelming majority of cases, microbiolites are formed at the sedimentation stage, and their morphology and type are determined by specific paleogeographic and paleoclimatic conditions.